Inter-relationship between firm growth and profitability in a context of economic crisis - Fuertes-Callén, Yolanda; Cuellar-Fernández, Beatriz (Journal of Business Economics and Management, 2019)
This paper examines the dynamics between growth and profitability in an economic crisis context by considering the endogeneity of this relationship. It also analyzes the role of innovation and export intensity in the growth-profit relationship. Using a large firm-level dataset comprising Spanish manufacturing companies during the pre-crisis (2000–2007) and the crisis (2008–2014) period, static and dynamic panel data models are estimated. The analysis suggests the following results. First, in the short term, growth has a positive impact on profits, while the effect of profits on growth depends on the measure of growth used. So, employee’s growth requires previous profit but profit does not play a major role as determinant of sales growth. Second, profit rates are found to persist in the short term. In contrast, a reversion of turnover and employees growth rates is observed. Thirdly, the moderation analysis applied shows that the strategy that has enabled firms to grow is export. Moreover, the influence of the export intensity on profitability in the economic crisis period is obtained indirectly through sales and employee’s growth. Unlike expected, innovation efforts do not moderate the relationship between profitability and firm growth.